Factors that Influence Auditor Switching in Banks Listed on the BEI - Doni Prayoga; Akbar, Maulana; Salta, Salta (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to examine the impact of going concern audit opinion, financial distress, company complexity, institutional ownership, and company size on auditor switching. And in this research we also added a moderating variable, namely audit fees, to test the role of audit fees in moderating the relationship between factors that influence auditor switching. This research focuses on bank companies listed on the Indonesia Stock Exchange in 2019-2022. The data collection technique uses a purposive sampling method with a total of 164 data, taken from 41 banks listed on the Indonesia Stock Exchange. This research uses multiple linear regression analysis techniques and interaction tests or MRA (Moderated Regression Analysis). This calculation analysis was carried out with the help of SPSS software. The research results show that going concern audit opinion has a positive effect on auditor switching, while company complexity has a negative effect on auditor switching. However, factors such as financial distress, institutional ownership and company size have no influence on auditor change. Apart from that, the size of the audit fee does not moderate the relationship between the factors that influence a company's decision to change auditors.